United Nations peacekeeping in Africa since 1960 - MacQueen, Norrie, 1950- (London : Longman, 2002)
What are the internal and external factors which have caused so many African states to 'fail' and 'collapse'? How have developments in the broader international system affected conflicts in Africa? What determines 'success' and 'failure' in African peacekeeping? This comprehensive analysis of all UN peacekeeping in Africa combines broad theoretical ideas with careful historical narrative. The book explores the entirety of United Nations military intervention in Africa since its beginnings in the Congo in 1960 to the new operations of the twenty-first century. Describing the peacekeeping project on a region-by-region basis, Norrie Macqueen highlights throughout comparisons and contrasts within and between each part of Africa, and asks has it all been worthwhile? -- Publisher derscription.
1. The setting : the history, politics and law of United Nations engagement in Africa -- 2. Patrolling the ethnic frontier : central Africa -- 3. Managing delayed decolonization : southern Africa -- 4. Controlling the warlords : west Africa -- 5. Reconstructing and defining the post-Cold War state : the Horn of Africa -- 6. Making borders : trans-Saharan Africa -- 7. Conclusions : 'Firing into a continent' -- or making a difference?
Includes bibliographical references and index.
Keywords: United Nations. -- Peacekeeping Forces -- Africa; Since 1960; Conflict management -- Africa -- 1960-; International cooperation; International relations; History